Some theoretical and practical lessons to be learnt from Romania economic crisis challengesin Romania - ZAMAN, Gheorghe (Annals of Spiru Haret University. Economic Series, 2011)
The present article has as a main theme the complex mechanism regarding the evolution of world global economy crisis started back in 2008, and its present influence at the level of Romanian economy. This paper herein will analyze, in short, a few of the theoretical, methodological, practical and implementation challenges brought about by the crisis in Romania, as well as the likely ways to prevent, mitigate impacts and resist to its shocks or to go back to the path of a sustainable economic growth.